Embodiments of bitter narratives: constructing possible Indo-Caribbean identities through the karela. Issue 1 (1st September 2021) - Swamy, Priya; Lewis, Sarojini
Abstract : This critical conversation between multidisciplinary artist Sarojini Lewis and curator Priya Swamy explores the possibilities of exhibiting and telling histories of Indian indentured labour otherwise. Focusing on the installation Why Do You Have a Face Like a Sopropo? (Worldmuseum Rotterdam, 2020), Lewis details why and how she sees a bitter, resilient and uniquely shaped vegetable like bitter gourd ('karela' in Hindi, 'sopropo' in Sranang Tongo) as an extension of memory and ancestry. The authors begin by discussing the karela as an 'alternative text' (Mahabir 2009), before contextualising Lewis' wider artistic practice. They then discuss in depth the installation Why Do You Have a Face Like a Sopropo?, its implications, and its methods. Finally, as a form of conclusion, both authors reflect upon what it means to have worked on this installation together, from within their distinct positionalities, and what this may imply for Indian indentured labour histories and experiences in the context of global Indian diaspora narratives.